Corporate Governance On Agency Costs: A Field Study On The Syrian Joint Stock Companies - عمار, قصي; وقاف, يوسف (Latakia University Journal - Economic and Legal Sciences Series, 2023)
This research deals with the role of corporate governance in alleviating of agency problem in the companies that subject to the supervision of Syrian Commission on Financial Markets and Securities, during (2012-2021). The main objective is to study the relationship between the mechanisms of corporate governance (managerial ownership, ownership of major shareholders, board size, board independency, CEO duality and debt financing), and the assets turnover as an inverse measure for the agency cost. The researchers used a hypothetical-deductive approach to formulate the hypotheses, and in order to test them, the researchers used panel data. Results indicate that managérial ownership, separation between the board chairman and the executive director and debt financing play an important role in alleviating agency costs in the Syrian business environment. While the role of the board of directors depends on the direct relationship between its size and company' size. There is an inverse effect of ownership of major shareholders on agency costs. Finally, there is no impact of the board independency on agency costs.